Needs of farmers for guidance publication to the development of agricultural extension in Anbar, Iraq - Man, Norsida; Abd. Latif, Ismail; Mohd Nawi, Nolila; Salih, Majeed Hadi; Mohammed, Sarah Jasim (The International Institute for Science, Technology and Education (IISTE), 2015)
Guidance publication one of the most important sources of information for farmers about crop techniques,knowledge, and cropping information to get high productivity. Targeted research to asses the relationship between the wheat grower information level and recommendations of the Scientific pamphlet of wheat and some independent variables studied, as well as identify social characteristics, and functional for extension workers, and determine the reasons for non-use of the indicative releases from the point of view of agricultural workers. Iraq determines the research community in all extension agents to maintain a (92 Advisor) and sample farmer b (145 farms) of village farmers discussed (414) farms, selected a random sample of 35% of the province's villages and all of the following villages: ( Qusaiba village, Parwana and sons Hassan and corner Walnhih , Znkorh and the village of Black Hill).Data were collected by personal interview from 3 January to 28 March 2014 through the resolution, analysis of research data on the frequencies, percentages and arithmetic mean, standard deviation, range, as any simple correlation coefficient. The most significant results show that (18.6%) are small and that the information category (31, 7%), them with the information medium, and that (49.6%) They are with high information. Moral relationship at 0.01 level (0.05) between the level of agricultural information and (Gender, age, cultural openness, sources of information), and non-moral moral level 0, 05 for each of the following independent variables (marital status, Farming, engagement, agricultural property type, participate in outreach activities, the trend towards agricultural innovations).